Forward genetic analysis of Toll-like receptor responses in wild-derived mice reveals a novel antiinflammatory role for IRAK1BP1 - Conner, James R. (The Rockefeller University Press, 2008)
Although inflammatory cytokines produced by activation of Toll-like receptors (TLRs) are essential for early host defense against infection, they also mediate a vast array of pathologies, including autoimmune disease, hypersensitivity reactions, and sepsis. Thus, numerous regulatory mechanisms exist in parallel with proinflammatory pathways to prevent excessive release of these potent effector molecules. We report elucidation of a novel regulatory function for interleukin receptor–associated kinase (IRAK)-1 binding protein 1 (IRAK1BP1, also known as SIMPL) through quantitative trait locus mapping of the TLR response in wild-derived mouse strains. This gene emerged as a negative regulator of TLR2-mediated interleukin (IL)-6 production in MOLF/Ei mice, which expressed IRAK1BP1 mRNA in an allele-specific manner when crossed with the C57BL/6J strain. Human peripheral blood mononuclear cells and primary macrophages from two other wild-derived mouse strains also induced IRAK1BP1 mRNA by 4 hours after stimulation with agonists of various TLRs. Examination of its effects on IL-6 and other cytokines demonstrated that IRAK1BP1 regulates transcription of a specific subset of TLR-responsive genes, producing an overall antiinflammatory profile. Our results reveal that IRAK1BP1 is a critical factor in preventing dangerous overproduction of proinflammatory cytokines by the innate immune system and in influencing the specificity of TLR responses. Furthermore, these results show that the genetic diversity of wild-derived mouse strains makes them a valuable model of important human gene functions that have been lost in some laboratory-inbred strains.